2018
DOI: 10.1111/mec.14571
|View full text |Cite
|
Sign up to set email alerts
|

Selection outweighs drift at a fine scale: Lack of MHC differentiation within a family living lizard across geographically close but disconnected rocky outcrops

Abstract: The highly polymorphic genes of the major histocompatibility complex (MHC) are involved in disease resistance, mate choice and kin recognition. Therefore, they are widely used markers for investigating adaptive variation. Although selection is the key driver, gene flow and genetic drift also influence adaptive genetic variation, sometimes in opposing ways and with consequences for adaptive potential. To further understand the processes that generate MHC variation, it is helpful to compare variation at the MHC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 106 publications
0
12
0
Order By: Relevance
“…Looking at this another way, in Maria Island devils at least, inbreeding appears to be a sufficiently powerful process to drive the diversity of loci that are probably also experiencing selection. With the growing availability of various data sets in molecular ecology, we are increasingly able to ask questions about the extent to which neutral vs. adaptive processes shape patterns of diversity in natural populations (Grueber et al, 2013;Pearson, Bull, & Gardner, 2018;Sutton, Nakagawa, Robertson, & Jamieson, 2011). This is particularly relevant in small populations, which experience significant genetic drift and are under threat from novel environmental and ecological pressures (Gilroy, Phillips, Richardson, & van Oosterhout, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Looking at this another way, in Maria Island devils at least, inbreeding appears to be a sufficiently powerful process to drive the diversity of loci that are probably also experiencing selection. With the growing availability of various data sets in molecular ecology, we are increasingly able to ask questions about the extent to which neutral vs. adaptive processes shape patterns of diversity in natural populations (Grueber et al, 2013;Pearson, Bull, & Gardner, 2018;Sutton, Nakagawa, Robertson, & Jamieson, 2011). This is particularly relevant in small populations, which experience significant genetic drift and are under threat from novel environmental and ecological pressures (Gilroy, Phillips, Richardson, & van Oosterhout, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We found evidence for a consistent pattern of significant fine‐scale genetic structure within seven close but disconnected E. stokesii sampling sites. Our results extend that of an earlier study that found significant genetic structure among three of the sites we sampled (Pearson et al ) and suggest similar ecological and evolutionary processes may have occurred across the seven sites. The significant genetic differentiation we observed is likely to be due to the family group social structure and limited dispersal exhibited in this species.…”
Section: Discussionmentioning
confidence: 99%
“…We would expect a much sharper break between the clusters if assortative mating is invoked. In addition, previous work on MHC in this species from these locations did not uncover any differentiation at MHC (Pearson et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers successfully obtained sequence information and analyzed their genetic structure and population dynamics [4][5][6][7]. Later, when analyzing the MHC of some endangered or newly discovered species [8,9], people further studied from the aspects of species relationship, survival and reproduction, and disease resistance [10][11][12][13][14][15][16][17].…”
mentioning
confidence: 99%